Direct allylation of in situ generated aldehyde acyl anions by synergistic NHC and palladium catalysis - Ahire, Milind M.; Mhaske, Santosh B. (Angewandte Chemie-International Edition, 2014)
The direct regioselective allylation of in situ generated aldehyde acyl anions has been achieved by synergistic NHC and Pd catalysis. It provides an efficient access to valuable beta,gamma-unsaturated ketones under mild reaction conditions starting from easily accessible allylic carbonates and aldehydes without any preactivation. The synergistic catalysis method demonstrated herein adds a new dimension to the area of metal-mediated C allylation.
Keywords: aldehyde umpolung; C allylation; N-heterocyclic carbenes; Palladium; synergistic catalysis

Synthesis of o-methyl trifluoromethyl sulfide substituted benzophenones via 1,2-difunctionalization of aryne by insertion into the C-C bond - Ahire, Milind M.; Khan, Ruhima; Mhaske, Santosh B. (Organic Letters, 2017)
An efficient process for the preparation of valuable o-methyl trifluoromethyi sulfide substituted benzopheriones has been developed. The transition-metal-free method features insertion of aryne into a C-C sigma-bond under mild reaction conditions for the first time to achieve ortho-difunctionalized arenes containing a pharmaceutically important trifluoromethylthio functional group. A wide substrate, scope has been demonstrated for the developed protocol.

Synthesis of succinimide derivatives by NHC-catalyzed stetter reaction of aromatic aldehydes with N-substituted itaconimides - Ahire, Milind M.; Mhaske, Santosh B. (ACS Omega, 2017)
An N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aromatic aldehydes with N-substituted itaconimides has been developed. A delicate balance between the Stetter reaction and the competing isomerization of the itaconimide double bond has been achieved in this operationally simple reaction to afford valuable new succinimide derivatives containing 1,4 and 1,5 dicarbonyl scaffolds in good to excellent yields. The reaction tolerates variable substituents on both aldehydes and N-substituted itaconimides.

Application of sulfur ylides in 1,2-difunctionalization of arynes via insertion into a C-S sigma-bond - Ahire, Milind M.; Thoke, Mahesh B.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel reactivity of sulfur ylides has been demonstrated in a transition-metal-free protocol to access ortho-substituted thioanisole derivatives by insertion of arynes into a C-S sigma-bond in moderate to good yields. The reaction involves the formation of C-C and C-S bonds and consecutive breaking of two C-S bonds under operationally mild reaction conditions.

Isa-NHC-catalyzed intermolecular stetter reaction of aromatic aldehydes with maleimides: an efficient access to 3-aroylsuccinimides - Ahire, Milind M.; Mhaske, Santosh B. (Tetrahedron, 2018)
An intermolecular Stetter reaction of aromatic aldehydes with maleimides has been developed using thiazolylidene salt derived Isa-NHC as an efficient organocatalyst. The synthesized Stetter products "3-aroylsuccinimides" are important building blocks for the synthesis of natural products and bioactive compounds. The reaction conditions are mild, and various substituents on aromatic aldehyde and maleimide nitrogen were tolerated. (C) 2018 Elsevier Ltd. All rights reserved.

Stereoselective construction of deoxy-cruciferane alkaloids by NHC-catalyzed intramolecular annulation of homoenolate with quinazolinone - Ahire, Milind M.; Pol, Mahesh D.; Kavale, Dattatry S; Gonnade, Rajesh G.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2019)
Chiral N-heterocyclic carbene (NHC)-catalyzed intramolecular [3 + 2] annulation of enals with an unactivated imine moiety of quinazolinone via formal homoenolate cycloaddition has been demonstrated. It is an excellent approach for stereoselective syntheses of deoxy-cruciferane alkaloids comprising a biologically important pyrroloindoline scaffold. Notably, this is the first report on the NHC-catalyzed asymmetric intramolecular homoenolate annulation with cyclic N-acyl amidine.

Construction of unique SCF3-containing building blocks via allylic alkylation of Morita-Baylis-Hillman adducts - Halder, Priyanka; Pol, Mahesh D.; Ahire, Milind M.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2020)
Lewis base-catalyzed allylic alkylation of Morita-Baylis-Hillman adducts with alpha-SCF3 ketones has been demonstrated. The developed strategy provides efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesufinyl motif on a stereogenic carbon.